The formation of AlF by radiative association - Andreazza, C. M. [UNESP]; Almeida, A. A. de (Oxford University Press, 2014)
The formation of the aluminium monofluoride molecule AlF by radiative association of the Al and F atoms is estimated. The radiative association of Al(P-2) and F(P-2) atoms is found to be dominated by the approach along the A(1) potential energy curve accompanied by spontaneous emission into the X-1 Sigma(+) ground state of the AlF. For temperatures ranging from 300 to 14 000 K, the rate coefficients are found to vary from 1.35 x 10(-17) to 9.31 x 10(-16) cm(3) s(-1), respectively. These values indicate that only a small amount of AlF molecules can be formed by radiative association in the inner envelope of carbon-rich stars and other hostile environments.
Keywords: atomic data; atomic processes; circumstellar matter; ISM: molecules